Long‐term follow‐up demonstrates curative potential of autologous stem cell transplantation for relapsed follicular lymphoma. (10th January 2023) - Puckrin, Robert; Chua, Neil; Chin, Kelly; Peters, Anthea; Duggan, Peter; Shafey, Mona; Storek, Jan; Jamani, Kareem; Owen, Carolyn; Stewart, Douglas
Summary: Although autologous stem cell transplantation (ASCT) can achieve durable responses in eligible patients with follicular lymphoma (FL), long‐term follow‐up is needed to determine if it has curative potential. This retrospective, multicenter study included 162 patients who received ASCT for relapsed FL in Alberta, Canada. With a median (range) follow‐up time of 12.5 years (0.1–27.9), the 12‐year time‐to‐progression (TTP) was 57% (95% confidence interval [CI] 49%–65%), time‐to‐next‐treatment was 61% (95% CI 52%–69%), progression‐free survival was 51% (95% CI 42%–59%) and overall survival was 69% (95% CI 60%–76%). A plateau emerged on the TTP curve at 57% starting 9 years after ASCT with no relapses occurring beyond this timepoint. Ten patients remained in remission 20 years or more after ASCT. Patients undergoing ASCT at first or second relapse had superior outcomes compared to third or later relapse (12‐year TTP 61% vs. 34%), as did patients without progression of disease within 24 months (POD24) of frontline treatment versus those with POD24 (12‐year TTP 67% vs. 50%). ASCT achieves high rates of durable remission in relapsed FL, with long‐term follow‐up revealing that more than 50% of transplanted patients may be functionally cured of their lymphoma. The optimal timing to consider ASCT is at first or second relapse, regardless of POD24 status.